Integration and Alienation: Cross-Cultural Adaptation of Chinese Immigrants in Iceland - Xin Chen 1998- (2023)
Cultural adaptation refers to the cultural change caused by touching two or more different cultures. It is an inevitable stage for Chinese immigrants in Iceland. Therefore, it is of great practical significance to study the cultural adaptation of Chinese immigrants in Iceland. From the perspective of sociology, this paper uses literature research, discourse analysis, and in-depth interview research methods to study Chinese immigrants. Through discourse analysis of the video text of "Dear Jiaqian" and in-depth interviews with 16 research objects, this paper discusses the cultural adaptation of Chinese immigrants in Iceland, as well as their status of integration or sorting in the whole Icelandic society, On this basis, the paper analyzes the external and internal factors that affect the cultural adaptation of Chinese immigrants, and puts forward the adaptation strategies of increasing the construction of social networks, creating a multicultural atmosphere, overcoming stereotypes, improving relevant policies and regulations, enhancing personal internal ability, and adjusting personal mentality.